Cytokine Induced Killer (CIK) Cells Based Adoptive Immunotherapy - Timalsena, S; Lamichhane, P P (Journal of Gandaki Medical College-Nepal, 2018)
Cytokine induced killer (CIK) cells has been increasingly used in adoptive immunotherapy against various cancers and viral infections. This review summarizes the basic overview of CIK cells as a therapeutic immunocyte. Herein, the basic concepts on CIK cells, their general characteristics, approaches in enhancing their functions, cytotoxic mechanism of CIK cells and their therapeutic benefits in tumors and viral infections are explored. J-GMC-N | Volume 11 | Issue 01 | January-June 2018, Page: 58-63